1980
DOI: 10.1159/000232657
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-Mediated Histamine Release from Whole Blood

Abstract: An automated spectrofluorometric histamine assay has been applied to the study of allergen-mediated histamine release on small samples of blood. Histamine released into the plasma following incubation of blood with grass pollen, house dust or cat dander was compared in 35 nonallergic controls and 43 atopic patients sensitive to these allergens by history, skin tests and a high RAST score. 14 of the patients suffering from hay fever were examined after completion of at least 1 year of preseasonal immunotherapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
(12 reference statements)
1
9
0
Order By: Relevance
“…Whole blood histamine release was rapidly elicited and attained the maximum within 5 min after the addition of allergen, while release from washed leukocytes was much slower. The result of allergen-induced release studied here was generally similar to that by Radermecker [7], although the maxi mum percent release in this study was elicited after 15 min incubation. The difference in the incubation time leading to the maximum release between his re sult and ours was unknown.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Whole blood histamine release was rapidly elicited and attained the maximum within 5 min after the addition of allergen, while release from washed leukocytes was much slower. The result of allergen-induced release studied here was generally similar to that by Radermecker [7], although the maxi mum percent release in this study was elicited after 15 min incubation. The difference in the incubation time leading to the maximum release between his re sult and ours was unknown.…”
Section: Discussionsupporting
confidence: 87%
“…In this study the release of histamine with allergen and anti-lgE was observed using whole blood. The result by Radermecker [7] demonstrated that the time course of allergen-mediat ed histamine release was different from that of washed leukocytes. Whole blood histamine release was rapidly elicited and attained the maximum within 5 min after the addition of allergen, while release from washed leukocytes was much slower.…”
Section: Discussionmentioning
confidence: 99%
“…With washed whole blood, any immunological release measured can only be attributed to IgE-mediated type I hypersensitivity. The problem of blanks posed by plasma in fluorimetric assays [6] is overcome. The use of dialysis is also avoided by the present procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Minor modifications of Siraganian's method have later been published, comprising histamine release from isolated basophils as well as from whole blood [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Matched venous blood placed in a lithium heparin tube was also challenged with allergen extracts and sheep antihuman IgE . Levels greater than 15% of total histamine available were considered as probably positive both for polyp tissue and peripheral blood (Norman et al 1973, Radermecker 1980. Fourteen patients had asthma, 4 hay fever and 13 had positive skin tests to one or more allergens (Drake-Lee & McLaughlan, in preparation).…”
Section: Introductionmentioning
confidence: 99%